Various Plants of Traditional Rituals: Ethnobotanical Research Among The Baduy Community - Johan Iskandar; Budiawati S. Iskandar (Department of Biology, Faculty of Mathematics and Sciences, Semarang State University . Ro, 2017)
On the basis of recent studies in many places of developing countries it has been revealed that the practices of conservation of biodiversity has strongly determined by traditional ecological knowledge, and beliefs or cosmos. The aim of the study namely to elucidate; (1) some traditional rituals in the swidden management system of the Baduy community; (2) various plants that have been used for performing some rituals in the swidden management system of the Baduy community; and (3) some functions of various plants that have been used in the rituals of the swidden management system of the Baduy community. A qualitative method with ethnobotanical approach was applied in this study. The result of study shows that 9 kinds of the traditional rituals that have been predominantly undertaken by the Baduy community in the management of swidden farming system. At least 50 plant species representing 28 families have been used for those performing traditional rituals. The main function of plants in the rituals is considered as the symbolic meaning and rational function. The result of study has been considered very important that the traditional ecological knowledge and beliefs must be considered to conserve biological diversity.